PWE-118 Hepatitis b testing practice: how widespread is household contact tracing?. (22nd June 2015) - Mathew, S; Pericleous, M; Al-Hillawi, L; O'Dowd, D; Nicholls, M; Atkins, M; Cheent, K; Berry, P; Lewis, H; Ala, A
Abstract : Introduction: Contact tracing in hepatitis B (HBV) is nationally and internationally advocated. Acute HBV is managed by Public Health England (PHE). However, the expectation and responsibility for contact tracing in chronic HBV lies predominately with primary care, with no formal implementation strategy or monitoring system in place. Method: The Surrey Pathology Partnership serves over 1 million individuals in South East England. We collected laboratory data from the past 10 years on all Hepatitis B Surface Antigen (HBsAg), and Core Antibody (total HBcAb) testing requests, to assess the uptake and efficacy of contact-tracing amongst those with HBV. We identified address and postcode data from hospital and community-based testing requests (excluding anonymised GUM data) to identify those individuals who had undergone household contact-testing for HBV. Results: In total, 119, 873 HBV (HBcAb +/- HBsAg) tests were undertaken between Jan 2005 and Jan 2015; 69, 256 HBsAg tests (+/- cAb) were subsequently identified with appropriate address and postcode information. HBsAg was detected (positive) in 851/69, 256 laboratory requests (0.01%); median age 36 years, Female 55%, with 661 individual patients diagnosed with HBV in this period (HBcAb+ 77%). Clinical indications for testing and the requesting speciality were poorly documented, but antenatal HBV testing was the predominant indication/specialty with 23, 719 requests. 159/661(24%) of HBsAg-positive cases were detected in primary care, 395/661 (60%) in Hospital outpatients (Gastro/Hepatology); 10/661 (1.5%) in Antenatal services and 3/661 (0.45%) in Prisons. 814 unique patient addresses were identified for 661 HBV positive patients; 54 HBV positive patients shared the same address (26 households, range 2–3/household), with an additional 203 negative HBsAg requests made in the remaining household contacts, with HBcAb evident in 18% of these individuals. Conclusion: NICE public health recommendations were issued in late 2012 to guide HBV testing practice, but its uptake is thought to be poor, and our data highlights the deficits that exist in contact-tracing, with close to 70% of household-contacts not offered testing. Although there are data-deficits to using recorded laboratory data, it provides a readily available and reproducible format to identify and monitor regional contact-testing practice. We hope to use this format to guide and monitor regional testing strategies. Disclosure of interest: None Declared.